Lietuvos knyga ir visuomenė XX amžiuje - Stonienė, Vanda (Knygotyra, 1998)
Lithuanian book history of the 20th century is usually divided into 4 historical periods: 1) the book at the beginning of the 20th century (1904-1918), 2) the book of the Republic of Lithuania (1918-1940), 3) the book of occupational regimes, and 4) the book of the period of political independence regained (since 1990). The present article deals with the development of Lithuanian book up to 1990. The history of the book during this century has not been investigated in a more exhaustive manner. Some review articles concerning certain periods have been published by a group of researchers (A. Glosienė, D. Kaunas, A. Navickienė, V. Stonienė) in monograph „Lithuanian Book: historical outline" (1996). In recent years more attention was paid to the investigations into the book of the Republic of Lithuania. In 1992 A. Glosienė defended her doctoral thesis „Book publishing and propagation in Lithuania of 1918-1940". Materials of this thesis were published in some articles of research journal „Knygotyra" („Book science“). V. Zukas, continuing such research, started publishing the series „Lithuanian publishing houses“.The history of Lithuanian book in the 20th century begins in May, 1904, when the ban on Lithuanian press in Latin characters was canceled. This cancellation created more favorable conditions for using Lithuanian press for the needs of national rebirth and political independence fight. As a result, Lithuanian intellectuals could unite into societies of publishers (Society of St. Casimir, Society of Lithuanian Scientific Research). Besides, new private publishers and book propagators appeared (P. Vileišis, M. Kukta, M. Piaseckaitė-Šlapelienė). As a result of their efforts, about 6,000 publications of Lithuanian press were produced up to 1918. During this period the first Lithuanian newspapers in Lithuania started: „Vilniaus žinios“, „Lietuvos ūkininkas“, journal „Draugija“, the first research periodical „Lietuvių tauta“.World War I and German occupation slowed down the work in the field of Lithuanian press, but German military failures and more active efforts of Lithuanian intellectuals stimulated publishers to continue their initiated plans.The regained political independence in 1918 created conditions for Lithuanian book to function freely. The number of published books increased every year (from 336 titles in 1919 up to 1,426 titles in 1938). The total number of publications during 20 years reached 25,000. A system of state support and commercial publishing institutions was created which was able to provide press production of different content and functions for Lithuanian society. Scientific and cultural efforts and achievements stimulated largely publishing special kinds of books – monographs, dictionaries, encyclopedias. The publication of original and translated books of fiction increased in number and their quality level became much higher. The scale and importance of periodical press increased too. In 1930, the number of periodicals reached 172: 142 Lithuanian, 13 German, 6 Polish, 3 Russian, 7 Jewish and 1 Esperanto.In 1940, the Soviet occupation ruined abruptly the independent Lithuanian publication system, introduced a state monopoly and crude Bolshevik censorship. A large part of Lithuanian cultural heritage was annihilated, many books of previous publishers were simply burnt, the main part of periodicals destructed. Nevertheless, thanks to many authors and publishers who morally resisted the occupational regime, its russification tendencies, a number of valuable publications appeared. In general, during Soviet occupational regime 84,430 titles of books were published (75% of them in Lithuanian, 20% in Russian, 5% in other languages). Alongside of these publications, anti-Soviet underground press should be mentioned; it was produced and propagated by resistance activists, guerrillas. „Chronicle of Lithuanian Catholic Church“ is a unique publication of such a kind. The underground press of the Soviet period contributed much to the fight for restoring Lithuanian independence.